Corporate Governance Mechanisms and Voluntary Disclosure - Saraswati, Erwin; Azzahra, Alfizah; Sagitaputri, Ananda (AKRUAL: JURNAL AKUNTANSI, 2020)
Corporate disclosure and corporate governance are two inseparable instruments of investor protection. This research sought to find evidence on how corporate governance mechanisms affect the extent of voluntary disclosures. Voluntary disclosures were measured using content analysis on published annual reports. The sample of this research consisted of 81 firm-year observations from 27 firms of consumer goods sector listed on Indonesian Stock Exchange from 2016 to 2018. Using multiple regression method, the result has shown that board size and board independence increase voluntary disclosures, indicating that the commissioners have effectively represented the interests of shareholders by monitoring and encouraging the management to increase disclosure. This research provided new evidence that family ownership increases voluntary disclosure, suggesting that family firms are more concerned by the costs of non-disclosure. Meanwhile, institutional ownership does not significantly affect voluntary disclosure.Â